Coscattering in next-to-minimal dark matter and split supersymmetry - F. Brümmer (Journal of High Energy Physics)
Abstract In some models of thermal relic dark matter, the relic abundance may be set by inelastic scattering processes (rather than annihilations) becoming inefficient as the universe cools down. This effect has been called coscattering. We present a procedure to numerically solve the full momentum-dependent Boltzmann equations in coscattering, which allows for a precise calculation of the dark matter relic density including the effects of early kinetic decoupling. We apply our method to a simple model, containing a fermionic SU(2) triplet and a fermionic singlet with electroweak-scale masses, at small triplet-singlet mixing. The relic density can be set by either coannihilation or, at values of the mixing angle θ ≲ 10−5, by coscattering. We identify the parameter ranges which give rise to the observed relic abundance. As a special case, we study bino-like dark matter in split supersymmetry at large μ.